SUPERVISI AKADEMIK KEPALA LEMBAGA PENDIDIKAN ISLAM DALAM PENINGKATAN KINERJA PERFORMA GURU - Muh Hambali; Arini Rosyidah; Djuwairiyah Djuwairiyah (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2023)
This research aims to provide an explanation of the urgency of the academic supervision strategy carried out by the head of the madrasa. Teacher performance is the policy line for the head of the madrasah in Lamongan. This study uses a qualitative approach with a case study design, madrasah in Lamongan. Data collection was carried out by interview, observation, and documentation techniques. Data analysis techniques include reduction, presentation, and drawing conclusions as well as checking the validity of the data by means of data triangulation techniques. The results of the study confirm that the strategy used by the madrasa head in improving teacher performance is by planning academic supervision starting from the head of the madrasa to forming a supervising team. Then the team that has been formed formulates goals, sets goals, makes schedules and reviews academic monitoring instruments. Then the planning of the academic supervision program is carried out routinely at the beginning of each new school year. The preparation of the academic supervision program includes the entire learning process, namely planning, implementing and evaluating learning.